Na2SO4 and MgSO4 salts during the Holocene period derived by high-resolution depth analysis of a Dome Fuji ice core - Iizuka, Yoshinori (Journal of Glaciology)
We analyzed the profiles of ionic chemical species in three 500mm sections of an ice core from Dome Fuji, Antarctica, dated 3.0, 8.9 and 13.3 kyr BP (before present), and compared the profiles to those in the surface snow. The 3.0 and 8.9 kyr sections are from the Holocene and the 13.3 kyr section slightly predates the Holocene. The analyses were done on 2mm thick slices within each section. At each depth, the primary ionic species were Na+, H+, Cl- and SO4^[2-]. The SO4^[2-], Na+ and Mg2+ levels varied with depth in each section over distances ranging from several millimeters to several centimeters. Also, the correlation coefficients between Na+ and SO4^[2-] and between Mg2+ and SO4^[2-] for each depth were 0.90 or greater, in contrast to the value of 0.59 or less in the surface snow (defined here as 0-3.4m from the surface). These results suggest that almost all Na+ and Mg2+ in the Holocene ice exists as Na2SO4 and MgSO4 salts, and the formation of these salts occurs not only in the atmosphere during transport, but also in the firn layer.